DIPLOMASI KEMANUSIAAN INTERNATIONAL COMMITTEE OF THE RED CROSS (ICRC) DALAM KONFLIK ETHIOPIA – TIGRAY 2020 – 2022 - Jordan, Benjamin; Olivia, Yessi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
This research aims to describe the humanitarian diplomacy carried out by the ICRC in handling the humanitarian crisis in the non-international armed conflict, Ethiopia - Tigray in the period 2020 - 2022. Violations of international humanitarian law by the parties to the conflict resulted in a humanitarian crisis, where many lives were lost, especially towards civilians. As a private organization operating in the humanitarian sector, the ICRC uses humanitarian diplomacy to protect and provide assistance to conflict victims, including the Ethiopia – Tigray conflict. This research uses qualitative research methods, by collecting data through document analysis techniques sourced from books, journals, reports and websites related to ICRC diplomacy in the Ethiopia - Tigray conflict. The theoretical framework used in this research is humanitarian diplomacy which discusses how humanitarian actors use diplomacy to influence state actors in order to gain access to communities affected by the crisis. The level of analysis used is the group level of analysis. The results of this research show that in order to handle the humanitarian crisis in the Ethiopia - Tigray conflict, the diplomatic approach used by the ICRC is to negotiate access to assistance for victims by conducting dialogue with the conflict parties. The ICRC also monitors and provides assistance by providing essential needs, rehabilitation of facilities and infrastructure, as well as food security programs for conflict victims. In addition, in protecting victims, the ICRC promotes international humanitarian law against local authorities. The effectiveness of ICRC diplomacy can be seen from the acceptance of ICRC humanitarian activities, and the achievements of ICRC aid operations in Ethiopia from year to year. Keywords Humanitarian Diplomacy, Humanitarian Crisis, ICRC, Non-International Armed Conflict